Church Fathers on the Sabbath and Sunday - Koberson Langhu (Fakultas Filsafat Universitas Advent Indonesia, 2022)
Christians do not share the same view about the seventh day Sabbath and Sunday. A minority of Christians considers the Sabbath as still binding while a large majority dismisses it. For the latter, the cessation of Sabbath observance is traced back to the apostles. They believe that Sunday has replaced the Sabbath on account of Christ’s resurrection. However, the New Testament and historical documents reveal that the eclipse of Sunday over the Sabbath did not begin with the apostles. This means that the change must have occurred sometime after the apostles. A group of significant church leaders and theologians called church fathers arose in the second century onward whose theological understanding had profound impact on the Christians. What were their understanding of the Sabbath and Sunday? Should their understanding be accepted as normative for Christians today? This study is based on literary research methodology. The findings clearly indicate that in the understanding of most church fathers, Sunday had eclipsed and replaced Sabbath in importance and practice for Christians.